The Implementation of Kolcaba's Comfort Self-Efficacy Theory on Anxiety in Hospital Patients: A Systematic Review - Sulistyorini Sulistyorini; Blacius Dedi; Tri Ismu Pujiyanto (Indonesian Journal of Global Health Research, 2026)
Hospitalization often causes physical and psychological stress in the form of pain, anxiety, and discomfort that impact the patient's quality of life. The application of Kolcaba's Comfort Theory combined with Bandura's concept of self-efficacy is believed to be able to increase comfort, reduce anxiety, and improve clinical outcomes for patients in the hospital. This systematic review aims to summarize empirical evidence regarding the implementation of Kolcaba's Comfort self-efficacy on patient anxiety and comfort in hospitals. The study used a systematic review approach with the PRISMA protocol. Literature searches were conducted through Google Scholar, Semantic Scholar, ProQuest, and ScienceDirect using keywords related to self-efficacy, patients, and Comfort Kolcaba . Included articles were publications from 2015–2025 with quantitative, qualitative, cross-sectional , RCT, and quasi-experimental designs . Of the 460 articles identified, 9 studies met the inclusion criteria for analysis. A total of 9 articles were synthesized based on the findings of the implementation of kolcaba's comfort self-efficacy theory on hospital patient anxiety. The review showed that integrating self-efficacy with Comfort Theory effectively reduced anxiety, depression, and pain, as well as improving comfort, quality of life, therapy adherence, self-care skills, and patient satisfaction. Interventions proven effective included humanistic care, the Clark comfortable nursing approach , and non-pharmacological therapies such as smartphone-based virtual reality. The implementation of Comfort Kolcaba self-efficacy contributed significantly to improving the holistic comfort of patients in the hospital, particularly in reducing anxiety.